Beyond Ireland’s Myth, Its Folklore, and Its Two-Dozen Indigenous Animals: Review of Animals in Irish Literature and Culture, ed. Kathryn Kirkpatrick and Borbála Faragó - Myers, Nathaniel (Humanimalia, 2017)
Kathryn Kirkpatrick and Borbála Faragó, eds. Animals in Irish Literature and Culture. Palgrave Studies in Animals and Literature. Basingstoke: Palgrave Macmillan, 2015. xviii + 270 pp. $90.00 hc, $69.99 e-book.